PERBEDAAN KONDISI LINGKUNGAN BERDASARKAN INCIDENCE RATE (IR) DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS MRANTI KABUPATEN PURWOREJO TAHUN 2017 - Grandiz Fairoza Yana; Suhartono Suhartono; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue fever or dengue hemorrhagic fever (DHF) is an infectious diseases that caused by dengue virus, which was transmitted to human by Aedes aegypti mosquito. DHF was a major problem because it often becomes an outbreak in Indonesia one of them in Purworejo District. In Purworejo the Incidence Rate level was fluctuated, include Pangenrejo village and Mudal village. The purpose of this research is to know the differences of evironmental condition between two villages. The type of this research is observational analytic, which was using Cross-sectional study approach with comparative study method. The population of this study is 2434 household. The sampling technique was using proportionate stratified random sampling, it’s obtained 105 sample household. The analysis data was using  Chi-square test and Mann Whitney test with 95% confidence level. The result showed that there are 4 environmental variables that had the differences like container characteristics (p=0,001), the presence of mosquito larvae (p=0,001), the container index (CI), and the utilization of anti-mosquito repellent (p=0,004). While the temperature environmental factor (p=0,217), humidity (p=0,483), population density (p=0,235), used wire netting in ventilation (p=0,890), the presence of fish (p=0,069),the presence of mosquito resting place (p=578), and the presence of  mosquito breeding place (p=0,667) did not show any difference. The conclusion in this research was urban village with high IR does not mean had worse environment condition more than urban village with low IR. This was evidenced from the results of existing studies 7 variables that states do not had differences in environmental conditions due to both areas had similar environmental conditions. The community was expected to pay more attention for potential environmental condition as breeding place by doing PSN and PJR at least once a week, PJB at least once a month and using anti-mosquito to reduce the bite of adult mosquitoes.